Alpha-synuclein mutations impair axonal regeneration in models of Parkinson's disease - Tönges, Lars (Frontiers Media S.A., 2014)
The dopaminergic (DAergic) nigrostriatal tract has an intrinsic regenerative capacity which can be impaired in Parkinson's disease (PD). Alpha-synuclein (aSyn) is a major pathogenic component in PD but its impact on DAergic axonal regeneration is largely unknown. In this study, we expressed pathogenic variants of human aSyn by means of recombinant adeno-associated viral vectors in experimental paradigms of DAergic regeneration. In a scratch lesion model in vitro, both aSyn(A30P) and aSyn(A53T) significantly reduced DAergic neurite regeneration and induced loss of TH-immunopositive cells while aSyn(WT) showed only minor cellular neurotoxic effects. The striatal density of TH-immunopositive axons in the striatal 6-OHDA lesion mouse model was attenuated only by aSyn(A30P). However, striatal expression levels of the regeneration marker GAP-43 in TH-immunopositive fibers were reduced by both aSyn(A30P) and aSyn(A53T), but not by aSyn(WT), which was associated with an activation of the ROCK signaling pathway. Nigral DAergic cell loss was only mildly enhanced by additional overexpression of aSyn variants. Our findings indicate that mutations of aSyn have a strong impact on the regenerative capacity of DAergic neurons, which may contribute to their pathogenic effects.